Apology as Dialogue and Appeal - Williams, D. H. (Defending and Defining the Faith: An Introduction to Early Christian Apologetic Literature, 2020)
This chapter presents a reading of the Octavius, which is cast as a transcription of an earlier dialogue that purportedly took place in Ostia between three lawyers and friends: Marcus Minucius Felix, Caecilius Natalis, and Octavius Januaris. The text is set in a dialogical format that is clearly meant to recall the philosophical dialogues of Cicero, though it is less of a dialogue as it is actually composed of two speeches: one by Caecilius, defending the pagan position; and one by Octavius the Christian. Minucius functions as the arbitrator between the two others, though his actual role is the narrator of the exchange. The three lawyers are on holiday in Ostia, chatting as they walk along the shoreline, when the subject turns to religion; their conversation becomes a debate presenting both sides of the pagan-vs.-Christian arguments as commonly portrayed at the end of the second century. The chapter also considers the work of Thracius Caecilianus Cyprianus, bishop of Carthage.
paid